Buckling behaviour of steel and composite beams at elevated temperatures - Ronny Budi Dharma (2008)
The objective of this research was to study the buckling behaviour of steel and composite beams at elevated temperatures. Both global buckling in the form of lateral torsional buckling and local buckling were studied. The first part of the study focused on the lateral torsional buckling behaviour of bare steel beams with an aim to develop design approaches for laterally unrestrained steel beams at elevated temperature. The second part focused on the local buckling behaviour which limits the ductility of beams. Both bare steel beams and composite deck slab with re-entrant steel decking were considered for the second part to investigate the ductility issue related to inelastic behaviour in the hogging moment regions under fire conditions and to propose the model of the moment-rotational relationships.